2019
DOI: 10.1186/s13014-019-1329-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a 3D surface imaging system for deep inspiration breath-hold patient positioning and intra-fraction monitoring

Abstract: Purpose To determine the accuracy of a surface guided radiotherapy (SGRT) system for positioning of breast cancer patients in breath-hold (BH) with respect to cone-beam computed tomography (CBCT). Secondly, to evaluate the thorax position stability during BHs with SGRT, when using an air-volume guidance system. Methods and materials Eighteen left-sided breast cancer patients were monitored with SGRT during CBCT and treatment, both in BH. CBCT scans were matched on the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 43 publications
3
49
3
2
Order By: Relevance
“…Kügele et al reported that the intrafractional reproducibility for tangential and locoregional treatment was as low as 1 mm (median over 40 patients) in all three translational directions, but during a single treatment session the maximum deviation was up to 5 mm, which resulted in large effects on the target coverage and OAR doses [70]. The accuracy of SGRT systems have been reported within 5 mm for DIBH positioning and monitoring [71], and are similar to those reported in studies using spirometrybased positioning [68].…”
Section: Breath-holdmentioning
confidence: 99%
“…Kügele et al reported that the intrafractional reproducibility for tangential and locoregional treatment was as low as 1 mm (median over 40 patients) in all three translational directions, but during a single treatment session the maximum deviation was up to 5 mm, which resulted in large effects on the target coverage and OAR doses [70]. The accuracy of SGRT systems have been reported within 5 mm for DIBH positioning and monitoring [71], and are similar to those reported in studies using spirometrybased positioning [68].…”
Section: Breath-holdmentioning
confidence: 99%
“…Surface guided radiation therapy (SGRT) offers the possibility to monitor patient movements in real-time using a non-invasive approach, without any additional radiation exposure. SGRT has also proven to be a reliable tool for patient positioning by complementing in-room laser-assisted positioning, as well as for intrafraction monitoring during breast radiotherapy [18][19][20][21]. Moreover, SGRT may even reduce the frequency of conventional imaging during breast DIBH RT [22].…”
Section: Introductionmentioning
confidence: 99%
“…These phantoms were validated with hybrid plan measurements and an end-to-end test of a VMAT- The phantoms were fully compliant with the AlignRT surface scanning system, which is increasingly used for setup of breast cancer patients at radiotherapy departments. 5,19,20 The shape and red color of the PLA resulted in a stable surface registration result. During RTT training and hardware and software upgrade verification of the surface scanning system, we now use the E2E breasts compared to the vender-provided geometric phantom.…”
Section: Discussionmentioning
confidence: 99%